Identification of miRNAs regulating MAPT expression and their analysis in plasma of patients with dementia - Piscopo, Paola; Grasso, Margherita; Manzini, Valeria; Zeni, Andrea; Castelluzzo, Michele; Fontana, Francesca; Talarico, Giuseppina; Castellano, Anna Elisa; Rivabene, Roberto; Crestini, Alessio; Bruno, Giuseppe; Ricci, Leonardo; et al. (Frontiers in Molecular Neuroscience, 2023)
Background. Dementia is one of the most common diseases in elderly people and hundreds of thousand new cases per year of Alzheimer’s disease (AD) are estimated. While the recent decade has seen significant advances in the development of novel biomarkers to identify dementias at their early stage, a great effort has been recently made to identify biomarkers able to improve differential diagnosis. However, only few potential candidates, mainly detectable in cerebrospinal fluid (CSF), have been described so far. Methods. We searched for miRNAs regulating MAPT translation. We employed a capture technology able to find the miRNAs directly bound to the MAPT transcript in cell lines. Afterwards, we evaluated the levels of these miRNAs in plasma samples from FTD (n= 42) and AD patients (n=33) and relative healthy controls (HCs) (n=42) by using qRT-PCR. Results. Firstly, we found all miRNAs that interact with the MAPT transcript. Ten miRNAs have been selected to verify their effect on Tau levels increasing or reducing miRNA levels by using cell transfections with plasmids expressing the miRNAs genes or LNA antagomiRs. Following the results obtained, miR-92a-3p, miR-320a and miR-320b were selected to analyse their levels in plasma samples of patients with FTD and AD respect to HCs. The analysis showed that the miR-92a-1-3p was under-expressed in both AD and FTD compared to HCs. Moreover, miR-320a was upregulated in FTD vs AD patients, particularly in men when we stratified by sex. Respect to HC, the only difference is showed in men with AD who have reduced levels of this miRNA. Instead, miR-320b is up-regulated in both dementias, but only patients with FTD maintain this trend in both genders. Conclusions. Our results seem to identify miR-92a-3p and miR-320a as possible good biomarkers to discriminate AD from HC, while miR-320b to discriminate FTD from HC, particularly in males. Combining three miRNAs improves the accuracy only in females, particularly for differential diagnosis (FTD vs AD) and to distinguish FTD from HC.